Commodification of Marriage Customs in The Settlement of Piyeung, Montasik Sub-District - Asmaul Husna; Muslim Zainuddin; Suarni (Winaya Inspirasi Nusantara Foundation, 2020)
Commodification refers to the transformation of relationships that were originally free from commerce into commercialized relationships. Within the Piyeung community, certain aspects of their traditional marriage procession have been affected by commodification, resulting in elements of their culture being valued and sold for profit. This commodification has led to a decrease in togetherness during the wedding ceremony, as certain tasks that were previously done collectively, such as applying henna, are now outsourced to professionals. The author of this study aims to investigate the changes brought about by commodification in the traditional marriage procession of the Piyeung community in Montasik District, as well as the community's perception of these changes. Through qualitative research methods such as observation, interviews, and documentation, it was found that the traditional marriage procession has undergone modifications to make it more visually appealing. Changes were observed in areas such as the processional route, henna application, attire, food preparation, and serving. The Piyeung community acknowledges that these changes can diminish togetherness and social solidarity, but also recognize the employment opportunities and efficiency.